Management of giant african snail achatina fulica (Bowdich) - Mridul Vinod P (Department of Agricultural Entomology, College of Agriculture, 2016)
A study on “Management of giant African snail Achatina fulica (Bowdich)” was conducted at Department of Agricultural Entomology, College of Agriculture, Vellayani, Thiruvananthapuram, during 2014-16. The objectives were to study the distribution of A. fulica and its natural enemies, if any and to develop effective management strategy using plant extracts, chemicals and pathogenic nematodes. In order to find out the distribution of giant African snail (GAS), a survey was conducted in ten panchayaths of Thiruvananthapuram district. Among the ten panchayaths surveyed, Pulimath and Vakkom panchayaths recorded highest number of adults and juveniles of GAS respectively. Flat headed worm/ hammer headed worm and crow pheasant, Centropus sinensis Stephans were recorded as natural enemies. The management study included evaluation of different baits and traps for attracting GAS and evaluation of different chemicals, botanicals and pathogenic nematodes against GAS. Among the different baits evaluated for GAS, papaya leaf pulp (0.5 kg) + jaggery (100 g) + wheat flour (0.5 kg) was identified as best treatment with highest number of individuals attracted (11.65). Mud pot with fermented bait (wheat flour 500g + jaggery 200g + yeast) and copper sulphate 6% as poison was found to be superior trap over others, with 20 snails trapped per pot. Among different chemicals evaluated, copper sulphate 5% showed a quicker mortality (43.07 per cent) at 24 hours after treatment (HAT). The effect was continued and at 72 HAT, copper sulphate 5% shown significantly higher per cent mortality (93.33) over others and which was followed by copper oxychloride 4% and copper hydroxide 4% with, a mortality of 80 per cent. Results of the experiment to evaluate ovicidal action of chemicals against GAS revealed that, none of the chemicals found effective. The copper sulphate 5% was found to be the best poison bait among different baits evaluated with 80.29 and 88.71 per cent mortality of GAS at 24 HAT and 48 HAT respectively. The treatments: spinosad 45 SC @ 0.60 ml L-1 (T2), spinosad 45 SC @ 0.90 ml L-1 (T3), carbosulfan 25 EC @ 2.00 ml L-1 (T8), carbosulfan 25 EC @ 3.00 ml L-1(T9), chlorpyriphos 20 EC @ 6.00 ml L-1 (T12), metaldehyde @ 6.00 g m-2 (T21), copper sulphate @ 3.00 % (T23) and copper sulphate @ 5.00 % (T24) recorded 100 per cent mortality of snails at 72 HAT in the laboratory. The laboratory evaluation of eight botanicals at varying concentrations revealed that, they were not effective in causing mortality, ovicidal action and antifeedant effect against A. fulica. But comparitively higher per cent leaf area protection was observed for Azadirachta indica seed extract @ 15 %, Annona squamosa seed extract @ 15 % and Lantana camara leaf extract @ 25%, among which A. indica seed extract @ 15 % was found to be significantly superior to other treatments. Two species of nematodes from the genus Heterorhabditis (H. bacteriophora and H. indica), three species from the genus Steinernema (S. abbasi, S. bicornutum and S. carpocapsae) and two species from Rhabditis were tested against GAS. However, these nematodes were nonpathogenic to A. fuica. The study concluded with the following results. Higher population of adults and juveniles of GAS was observed from Pulimath and Vakkom panchayaths respectively. Papaya leaf pulp (0.5 kg) + jaggery (100 g) + wheat flour (0.5 kg) was the best bait evaluated against GAS. Mud pot with fermented bait and poison was superior to other traps evaluated. Copper oxychloride 4%, copper hydroxide 4% and copper sulphate 5% were effective chemicals evaluated against GAS. Copper sulphate 5% was found to be the best treatment among various chemicals evaluated as poison baits. Spinosad 45 SC @ 0.60 ml L-1 and 0.90 ml L-1, carbosulfan 25 EC @ 2.00 ml L-1 and 3.00ml L-1, chlorpyriphos 20 EC @ 6.00 ml L-1, metaldehyde @ 6.00 g m-2and copper sulphate 3% were also identified as effective poison baits under laboratory conditions.